What the manifesto manifests: Fredric Jameson, Wyndham Lewis, and the problem with 'An American Utopia'. Issue 6 (3rd June 2022) - Porteous, Richard
ABSTRACT: In his essay 'An American Utopia' (2016) Fredric Jameson advances a reflexive usage of the manifesto genre. Rather than simply announcing a new political agenda, Jameson uses rhetoric familiar from twentieth-century socialism to deliberately elicit a negative response from his readers. Using his writing to provoke and then point to a widespread aversion to group membership, Jameson situates himself in the aftermath of so many failed twentieth-century revolutionary traditions, and demonstrates, through his textual experiment, the coercive workings of an alternative strategy. In a play of manifestation, the manifesto manifests a reaction that it harnesses to illustrate its point. Rather than focusing on the universal army itself, I am interested in Jameson's reflexive rhetorical strategy, a game of stimuli-and-response that itself has an artistic and political genealogy. From this perspective 'An American Utopia' is less like The Communist Manifesto, and rather more like Wyndham Lewis's 1914 'Vorticist Manifesto', a modernist precursor both to Jameson's reflexive usage of the genre and its positing of a widespread, violent anti-sociality. I use this comparison between Jameson and Lewis as a vantage point from which some of the problems with Jameson's innovative strategy can more clearly be discerned.